2017
DOI: 10.1002/ajmg.b.32595
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular risk factors within the newly identified primate‐specific exon of the SAP97/DLG1 gene in the 3q29 schizophrenia‐associated locus

Abstract: The synapse-associated protein 97/discs, large homolog 1 of Drosophila (DLG1) gene encodes synaptic scaffold PDZ proteins interacting with ionotropic glutamate receptors including the N-methyl-D-aspartate type glutamate receptor (NMDAR) that is presumed to be hypoactive in brains of patients with schizophrenia. The DLG1 gene resides in the chromosomal position 3q29, the microdeletion of which confers a 40-fold increase in the risk for schizophrenia. In the present study, we performed genetic association analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…In this study, we have assessed the potential association of the rs3915512 polymorphism of the SAP97 gene with schizophrenia. However, the results revealed that there was no significant difference in genotype and allele distributions between the patients with schizophrenia and the healthy controls ( P > 0.05), which was inconsistent with the results of a previous Japanese cohort study from the Hondo area by Uezato et al ( 12 ). Moreover, the allelic frequencies of rs3915512 in the present study (A:T = 0.29: 0.71 in the cases and A:T = 0.28:0.72 in the controls), were markedly different from those in the Japanese Hondo cohort from a previous study (A:T = 0.63:0.37 in the cases and A:T = 0.66: 0.34 in the controls) ( 12 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, we have assessed the potential association of the rs3915512 polymorphism of the SAP97 gene with schizophrenia. However, the results revealed that there was no significant difference in genotype and allele distributions between the patients with schizophrenia and the healthy controls ( P > 0.05), which was inconsistent with the results of a previous Japanese cohort study from the Hondo area by Uezato et al ( 12 ). Moreover, the allelic frequencies of rs3915512 in the present study (A:T = 0.29: 0.71 in the cases and A:T = 0.28:0.72 in the controls), were markedly different from those in the Japanese Hondo cohort from a previous study (A:T = 0.63:0.37 in the cases and A:T = 0.66: 0.34 in the controls) ( 12 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, studies have shown that changing the structure of SAP97 would alter the binding affinity with its ligands and affect the transport of glutamate ( 11 ), which has been identified to play a key role in schizophrenia ( 6 ). A recent Japanese case-control study provided evidence of the relationship between the rs3915512 polymorphism of the SAP97 gene and schizophrenia ( 12 ). However, SAP97 gene polymorphisms have not been studied in schizophrenia patients of the Han Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…DLG1 has previously been associated with schizophrenia (Sato, Shimazu, Yamamoto, & Nishikawa, ; Toyooka et al, ; Uezato et al, , , ). The variant found in our patient was identified in a study of 234 unrelated cases with schizophrenia and 272 unrelated controls from the United Kingdom (Carroll et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…including those with roles in neuron proliferation, differentiation, cell-cell interaction, intraneuronal transport, synaptogenesis, primary axonogenesis, and axon guidance (Dlg1,Myt1l,Ptprs,Dctn2,Rgs7). Further, some genes are genetically linked to psychiatric disorders such as schizophrenia (Dlg1, Myt1l) (Lee et al, 2012;Uezato et al, 2017), autism spectrum disorder (Myt1l) (Meyer et al, 2012;Wang et al, 2016) and panic disorder (Rgs7) (Hohoff et al, 2009). Other genes from this list are linked to various types of cancer (Pnck,Calu,Vav2,Kif3a,Adgrf5,N4bp2l2).…”
Section: Loss Of Neat1 Affects Alternative Splicing Of Genes Involvedmentioning
confidence: 99%